Predictive factors of alcohol initiation among Brazilian adolescents: assessing the role of attitudes, decision-making, communication, and resistance skills - Juliana Y. Valente; Sheila C. Caetano; Miguel Henrique da Silva dos Santos; Zila M. Sanchez (Brazilian Journal of Psychiatry)
Objective: To evaluate whether attitudes toward drug use, as well as decision-making, communication, and alcohol resistance skills, act as predictors of alcohol use and binge drinking initiation among Brazilian students, considering sex differences. Methods: In a longitudinal sample of 1,103 seventh-grade students from 15 Brazilian public schools, we explored if attitudes toward drug use and decision-making, communication, and alcohol resistance skills at baseline predicted alcohol outcomes 9 months later. Results: Lower levels of resistance skills (i.e., ORboys = 0.29; 95%CI 0.12-0.70) and positive attitudes toward drugs (i.e., ORgirls: = 1.41; 95%CI 1.02-1.94) were predictors of alcohol use onset and binge drinking, independently of sex. Decision-making predicted binge drinking initiation, but only for girls (OR = 0.73; 95%CI 0.59-0.91). Negative attitudes toward drugs were a risk factor for alcohol use initiation, but only for boys (OR = 0.78; 95%CI 0.64-0.95). Conclusion: Our findings highlight the importance of understanding the predictors of alcohol initiation in adolescents, to inform which key components preventive programs should address in their activities to achieve the expected preventive outcomes.